Pengaruh Servicescape dan Service Quality terhadap Customer Satisfaction pada The Cups & Co Cabang Iskandar Muda - Putra, Irwansyah; Fandy, Danang Alif (Mahesa Research Center, 2025)
The purpose of this study is to find out and analyze the partial influence of servicescape on customer satisfaction, to find out and analyze the partial influence of service quality on customer satisfaction and to find out and analyze the simultaneous influence of servicescape and service quality on customer satisfaction at The Cups Co Iskandar Muda Branch. The population in this study is 1,426 customers visiting The Cups Co Iskandar Muda Branch. The sample in the study was 93 people who were taken using the slovin formula. The data collection technique used in this study was carried out by distributing questionnaires. The analysis techniques used in this study are multiple linear regression, partial test (t-test), simultaneous signification test (F-test) and determination coefficient. The results of the study show that servicescape has an effect on customer satisfaction, service quality has an effect on customer satisfaction and servicescape and service quality has an effect on customer satisfaction at The Cups Co Iskandar Muda Branch.